Shannon, Atlantic Lives - A Comparative Approach To Early America - Long, Michael (Teaching History: A Journal of Methods, 2005)
Some of the best ideas for the teaching of history come from those people who have devoted their lives to teaching the subject matter. Professor Timothy Shannon at Gettysburg College in Pennsylvania has recognized the need for a comprehensive textbook devoted to the Atlantic World and its place in the study of colonial America. Atlantic Lives is the result of that effort. His work presents a history of the Atlantic World from 1450 through 1830 with book chapters roughly following a chronological order. The book's design provides for a thematic approach to the study of colonial American settlement.